2007
DOI: 10.1007/s00425-007-0643-7
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-6-phosphate dehydrogenase plays a central role in modulating reduced glutathione levels in reed callus under salt stress

Abstract: In the present study, we investigated the role of glucose-6-phosphate dehydrogenase (G6PDH) in regulating the levels of reduced form of glutathione (GSH) to the tolerance of calli from two reed ecotypes, Phragmites communis Trin. dune reed (DR) and swamp reed (SR), in a long-term salt stress. G6PDH activity was higher in SR callus than that of DR callus under 50-150 mM NaCl treatments. In contrast, at higher NaCl concentrations (300-600 mM), G6PDH activity was lower in SR callus. A similar profile was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
45
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 56 publications
5
45
0
2
Order By: Relevance
“…It has been indicated that G6PDH plays a protective role against oxidative stress (Kletzien et al 1994, Pandolfi et al 1995. G6PDH is also involved in nitrogen assimilation (Oji et al 1985, Bowsher et al 1989, Esposito et al 2003, response to pathogenesis (Šindelář andŠindelářová 2002, Scharte et al 2009), metal toxicity (Esposito et al 1998), salt stress (Nemoto and Sasakuma, 2000, Liu et al 2007, Wang et al 2008 and combination of drought and heat stress (Rizhsky et al 2004). It was found that under salt stress G6PDH is involved in maintenance of intracellular reduced glutathione (GSH) in reed callus (Wang et al 2008) or NADPH content in olive plants (Valderrama et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It has been indicated that G6PDH plays a protective role against oxidative stress (Kletzien et al 1994, Pandolfi et al 1995. G6PDH is also involved in nitrogen assimilation (Oji et al 1985, Bowsher et al 1989, Esposito et al 2003, response to pathogenesis (Šindelář andŠindelářová 2002, Scharte et al 2009), metal toxicity (Esposito et al 1998), salt stress (Nemoto and Sasakuma, 2000, Liu et al 2007, Wang et al 2008 and combination of drought and heat stress (Rizhsky et al 2004). It was found that under salt stress G6PDH is involved in maintenance of intracellular reduced glutathione (GSH) in reed callus (Wang et al 2008) or NADPH content in olive plants (Valderrama et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that G6PDH was involved in the resistance to oxidative stress induced by salt stress (Liu et al 2007, Wang et al 2008a. In this study, the results showed that H 2 O 2 contents and G6PDH activity increased in red kidney bean roots under low NaCl concentration (50 -100 mM; Table 1).…”
Section: Discussionmentioning
confidence: 49%
“…The activity of G6PD, a key enzyme of the OPPP, increased in Arabidopsis plants upon high salinity stress. Consistently, G6PD activity was reported to be induced by NaCl treatment in other plant species (Valderrama et al, 2006;Wang et al, 2008). Importantly, loss of G6PD6 impinged on the redox status of glutathione and rendered plants more sensitive to salt stress.…”
Section: Discussionmentioning
confidence: 55%
“…In plants, G6PD activity is present in the plastids and cytosol (Debnam and Emes, 1999). G6PD activity has been positively correlated with environmental stresses such as salt stress (Valderrama et al, 2006;Wang et al, 2008), aluminum toxicity (Slaski et al, 2006), drought (Scharte et al, 2009), and infection by viral and fungal pathogens (Sindelár and Sindelárová, 2002;Scharte et al, 2009); by contrast, a decrease in chloroplastic G6PD activity has been shown to be beneficial for withstanding oxidative stress (Debnam et al, 2004). Thus, the role of G6PD in the stress response is currently unclear.…”
Section: Introductionmentioning
confidence: 99%